Asuhan Keperawatan Pada NY. M Dengan Anemia Di Ruang Muzdalifah Rumah Sakit Aisyiyah Kota Pariaman Tahun 2026 - Ani Depita Sari; Debby Silvia Dewi; Linda Marni; Hilma Yessi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Based on data from the World Health Organization (2025), the prevalence of anemia is widespread across various regions of the world, ranging from 52% to 80% of the global population. According to the Indonesian Health Survey (2023), the prevalence of anemia reached 16.3%, with a higher rate in women (18%) compared to men (14.4%). Meanwhile, data from the West Sumatra Health Office (2021) show that the average prevalence of anemia is higher in women, particularly among female groups at 29.8%, compared to 27.6% in men. In West Sumatra, the highest prevalence is found in Padang City at 14.5%. Medical record data from Aisyiyah Hospital in Pariaman City indicate that there were 96 anemia cases in 2025. The purpose of this case study is to obtain an overview of the implementation of nursing care for patients with anemia in the Muzdalifah Ward of Aisyiyah Hospital, Pariaman, in 2026. This study aims to enable students to apply comprehensive nursing care, especially for patients with anemia. The method used is a case study conducted over 5 days, from February 18 to 22, 2026, in the Muzdalifah Ward of Aisyiyah Hospital Pariaman, involving one patient (Mrs. M) with anemia. The results identified three nursing problems: ineffective peripheral tissue perfusion, fatigue, and risk of nutritional deficit, with the main priority being ineffective peripheral tissue perfusion. Evaluation over the 5-day period showed that ineffective peripheral tissue perfusion and fatigue were resolved, while the risk of nutritional deficit was partially resolved, with continued interventions carried out by the family. It is expected that patients and families maintain health, proper diet, and a healthy and regular lifestyle.